1993
DOI: 10.1007/bf00921959
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipid peroxide levels and myeloperoxidase activity in the vitreous of patients suffering from proliferative diabetic retinopathy

Abstract: Lipid peroxide (LPO) levels, as determined by high-performance liquid chromatography (HPLC) and by the thiobarbituric acid (TBA) method, and myeloperoxidase (MPO) activity in vitreous of patients vitrectomized because of proliferative diabetic retinopathy were compared with LPO levels and MPO activity in vitreous of patients with no vitreoretinal proliferation. Both LPO levels and MPO activity were significantly elevated in the vitreous of patients with fibrovascular vitreoretinal proliferations secondary to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…Patients with diabetic retinopathy have elevated blood levels of thio-barbituric acid reacting substances (a measure of oxidative stress and lipid peroxidation, and those in type I are higher than those in type II [6,7]. We have recently demonstrated that oxidative and inflammatory reactions are detectable in the vitreous body of eyes suffering from PDR and PVR with a higher inflammatory activity in diabetic eyes [8,9]. Tumor necrosis factor α (TNF-α), a cytokine also released during ischemia, which exerts changes of the bloodretina barrier, could be an important mediator of the disease process.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Patients with diabetic retinopathy have elevated blood levels of thio-barbituric acid reacting substances (a measure of oxidative stress and lipid peroxidation, and those in type I are higher than those in type II [6,7]. We have recently demonstrated that oxidative and inflammatory reactions are detectable in the vitreous body of eyes suffering from PDR and PVR with a higher inflammatory activity in diabetic eyes [8,9]. Tumor necrosis factor α (TNF-α), a cytokine also released during ischemia, which exerts changes of the bloodretina barrier, could be an important mediator of the disease process.…”
Section: Introductionmentioning
confidence: 96%
“…In previous studies we demonstrated elevated levels of lipid peroxides as thiobarbituric acid reacting substances and myeloperoxidase activity in the vitreous and epiretinal membranes from patients with PDR or PVR [8,9,25]. Activation of leukocytes leads to enhanced synthesis of cyclooxygenase and lipoxygenase which convert arachidonic acid into peroxide metabolites that further stimulate cytokine secretion through a positive feedback mechanism [26,27].…”
Section: Tumor Necrosis Factor-αmentioning
confidence: 99%
“…Ischemic diabetic retinal vascular occlusion, resulting from activated granulocytes and monocytes (24), is reversible and reperfusion has been documented angiographically in diabetic eyes (25). Elevated levels of ROI reaction products have been directly correlated with neovascularization in human (26) and rat (27) diabetic eyes, and in eyes with retinopathy of prematurity (28). Both ocular pathologies are strongly correlated with increased VEGF gene expression (8,9,(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…Increased serum lipid peroxides suggesting increased free radical activity is associated with retinopathy and this may have pathogenetic implications [14]. Increased lipid peroxide levels have also been observed in the vitreous of patients suffering from proliferative diabetic retinopathy [15]. Patients with diabetic nephropathy and retinopathy, but not neuropathy, have been found to have elevated plasma TBARS levels but no statistically significant difference was observed when compared with diabetic patients without microangiopathy.…”
Section: Discussionmentioning
confidence: 88%